Biosynthesis of silver nanoparticles using Lawsonia inermis and their biomedical application. Issue 7 (30th August 2022) - Alhomaidi, Eman; Jasim, Saade Abdalkareem; Amin, Hawraz Ibrahim M.; Lima Nobre, Marcos Augusto; Khatami, Mehrdad; Jalil, Abduladheem Turki; Hussain Dilfy, Saja
Abstract: Developing biosynthesis of silver nanoparticles (Ag‐NPs) using plant extract is an environmentally friendly method to reduce the use of harmful chemical substances. The green synthesis of Ag‐NPs by Lawsonia inermis extract and its cellular toxicity and the antimicrobial effect was studied. The physical and chemical properties of synthesised Ag‐NPs were investigated using UV‐visible spectroscopy, infrared spectroscopy, X‐ray diffraction (XRD), scanning, and transmission electron microscopy. The average size of Ag‐NPs was 40 nm. The XRD result shows peaks at 2 θ  = 38.07°, 44.26°, 64.43°, and 77.35° are related to the FCC structure of Ag‐NPs. Cytotoxicity of synthesised nanoparticles was evaluated by MTT toxicity test on breast cancer MCF7 cell line. Observations showed that the effect of cytotoxicity of nanoparticles on the studied cell line depended on concentration and time. The obtained IC50 was considered for cells at a dose of 250 μg/ml. Growth and survival rates decreased exponentially with the dose. Antimicrobial properties of Ag‐NPs synthesised with extract were investigated against Escherichia coli, Salmonella typhimurium, Bacillus cereus, and Staphylococcus aureus to calculate the minimum inhibitory concentration and the minimum bactericidal concentration of (MBC). The results showed that the synthesised Ag‐NPs and the plant extract have antimicrobial properties. The lowest concentration of Ag‐NPs that can inhibit the growth of bacterial strains was 25 μg/ml.